The Effectiveness of Implementing Computer-Based Learning Technology - Tonni Limbong; Romanus Damanik; Paska Marto Hasugian (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2025)
This study examines the application of computer-based learning technology at SMA Swasta 3 Bukit by utilizing the Google Form and Edmodo applications for attendance, learning materials, learning videos, independent assignments, and exams. The purpose of this study was to evaluate the impact of technology use on student motivation and learning outcomes. The method used is a descriptive qualitative approach with interviews and observations of teachers and students who use the application in learning activities. The data collected was analyzed to understand the effectiveness of the application of the technology. The main findings indicate that the use of technology can increase student engagement and ease of access to learning materials, but there are still obstacles related to the quality of internet connections and limited teacher training. The conclusion of this study is that technology can improve the quality of learning, but there needs to be an improvement in infrastructure and teacher training in order to optimize its use.